COST OF THE CREDIT IN PERU - Avelino Sánchez, Esteban Marino (2010)
How much foreign capital in Peru? This paper, based on studies of BCRP, gives an answer to this question. Before defining the concept of interest rate. Then, in turn, are analyzed nine macroeconomic factors that affect interest rates, the characteristics of the Peruvian market credit (distinguishing: dual currency market, lower interest rates offered for loans in dollars, customer type, interest rate spread, information asymmetry, lending technologies, competitive market structure of credit, performance guarantees, market development and trends of declining interest rates), microeconomic factors determining interest rates, cost of funds, credit risk, costs operational and expected utility, which determine interest rates, and finally other concepts that are added to the interest rate to disclose the rate of effective cost of credit. Therefore, the effective rate of the lending rate is lower than the actual cost of credit from financial companies in Peru.